Boxer Zhang Songxi and the Origins of the Internal-External School Concept - Wells, Marnix; Henning, Stanley E. (Revista de Artes Marciales Asiáticas, 2012)
Zhang Songxi was so highly respected for his boxing skills that the emperor’s grand secretary, Shen Yiguan (1531–1616), was inspired to write the Biography of Boxer Zhang Songxi. Later the historian Huang Zongxi (1610–1695) wrote an epitaph for a resistance fighter named Wang Zhengnan. In the biography he labeled both Wang and Zhang as practitioners of the “internal school of boxing,” versus what he called the Shaolin or “external school.” Since Shen Yiguan never mentioned Zhang as an internal- school practitioner, it appears that Huang was using the internal-external concept to symbolically express his dissatisfaction with China’s Manchu rulers. The Zhang Songxi biography provides some evidence that the internal-external school concept was more political than martial arts oriented.